2022
DOI: 10.1002/pssa.202100638
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Oxide‐Controlled InAlGaN/GaN High‐Electron‐Mobility Transistors Using Al2O3‐Based Insulated‐Gate Structures with H2O Vapor Pretreatment

Abstract: Herein, Al2O3/InAlGaN/GaN metal–insulator–semiconductor high‐electron‐mobility transistors (MIS‐HEMTs) using H2O vapor pretreatment to decrease the amount of deficient indium oxide (InOx) is successfully developed. InOx acts as an electron trap in the oxide on the surface of the InAlGaN barrier layer. It is clarified that when O2 plasma is used as an oxidant source for atomic‐layer‐deposited (ALD) Al2O3 (O2 plasma‐Al2O3), the forward breakdown voltage increases using the MIS‐HEMT, due to a high density and a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…We have previously reported that the improvement in the g m profile (the wider range of constant g m ) on InP-based HEMTs with a steam-annealed ultrathin-Al 2 O 3 gate dielectric (2 nm thick), due to a reduction in gate leakage current and an increase in forward breakdown voltage. 19) However, when using oxidant sources for ALD-Al 2 O 3 , the narrow band gap (∼3.4 eV) deficient indium oxide (InO x ) is generated in the surface-oxide of the In-based epitaxial layer, [20][21][22][23] thereby increasing the gate leakage current. 24) Thus, we developed inverted MOS-HEMTs with a surface-oxide-control (SOC) process that decreased the amount of InO x at the Al 2 O 3 /semiconductor interface.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the improvement in the g m profile (the wider range of constant g m ) on InP-based HEMTs with a steam-annealed ultrathin-Al 2 O 3 gate dielectric (2 nm thick), due to a reduction in gate leakage current and an increase in forward breakdown voltage. 19) However, when using oxidant sources for ALD-Al 2 O 3 , the narrow band gap (∼3.4 eV) deficient indium oxide (InO x ) is generated in the surface-oxide of the In-based epitaxial layer, [20][21][22][23] thereby increasing the gate leakage current. 24) Thus, we developed inverted MOS-HEMTs with a surface-oxide-control (SOC) process that decreased the amount of InO x at the Al 2 O 3 /semiconductor interface.…”
Section: Introductionmentioning
confidence: 99%
“…ate leakage current in RF devices is one of the most important issues to be solved for application in highpower amplifiers. 1,2) Al 2 O 3 films are an attractive gate dielectric for RF devices such as high electron mobility transistors (HEMTs) because of their wide band gap (∼7.0 eV), high dielectric constant (∼9.0), and high breakdown voltage (∼10 MV cm −1 ). [3][4][5][6][7][8][9] Furthermore, it is necessary for RF devices to optimize the thickness of Al 2 O 3 films to suppress the gate leakage current and maximize transconductance simultaneously.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Furthermore, it is necessary for RF devices to optimize the thickness of Al 2 O 3 films to suppress the gate leakage current and maximize transconductance simultaneously. 1,10) Thus, atomic layer deposited (ALD)-Al 2 O 3 is required for high-frequency RF devices, especially in sub-THz applications. [11][12][13] Furthermore, ALD-Al 2 O 3 is also used in advanced packaging such as surface-activated bonding (SAB) of heterogeneous wafers due to the thickness controllability for nano-adhesion layers and relatively high thermal conductivity.…”
mentioning
confidence: 99%
“…Thus, it is considered that the lattice disorder in bond lengths and angles 29) was induced by plasma damages at the surface of InGaP, leading to mobility degradation. 30) On the other hand, Al 2 O 3 gate dielectrics deposited by remote plasma ALD on the InGaP was effective to suppress these damages during SiN deposition. Therefore, R sh increase was suppressed by an insulated-gate HEMTs (SiN/Al 2 O 3 passivation), particularly after steam annealing (211 Ω/sq.…”
mentioning
confidence: 99%
“…This effect is important in terms of the input dynamic range at forward bias for high-power RF devices. 30,31) The drain current versus drain voltage (I d -V d ) characteristics of an insulated-gate HEMT and Schottky-gate HEMT, are shown in Figs. 4(a) and 4(b), respectively.…”
mentioning
confidence: 99%